The Effect of Product Quality and Price on Customer Satisfaction at Yulia Citra Furniture - Agustin, Yulia Citra; Sari, Ulfa Nurliana; Rosadi, Andri Asoka Sidantara (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This research was conducted on consumers of Yulia Citra Furniture, West Bandung Regency. The purpose of this research is to find out how much influence the influence of Product Quality and Price has on Consumer Satisfaction in purchasing both partially and simultaneously at Yulia Citra Furniture. The method used in this research is descriptive method and associative method. The unit of analysis in this study is the individual, namely consumers at Yulia Citra Furniture. The samples in this study were 129 respondents. The analytical method used is path analysis, multiple linear analysis, validity, and reliability tests of the research instruments are also carried out. Based on the results of the study indicate that there is a significant effect either partially or simultaneously on the independent variables (product quality and price) on (customer satisfaction). The implication of this research is that Yulia Citra Furniture should maintain product quality and price, because these two things affect future consumer judgments about consumer satisfaction which can attract the attention of customers who care about this, because businesses must have unique characteristics, and it is important to adjust suggestions with the context of the business being run.